2018
DOI: 10.1029/2018gl077760
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Radiation Hazard Observed by RAD on the Surface of Mars During the September 2017 Solar Particle Event

Abstract: We report dosimetric quantities measured by the Mars Science Laboratory Radiation Assessment Detector (RAD) on the surface of Mars during the 10–12 September 2017 solar particle event. Despite 23 g/cm2 of CO2 shielding provided by the atmosphere above RAD, dose rates rose above background galactic cosmic ray levels by factors of 2 to 3 over the course of several hours and leveled off at sustained peak rates for about 12 hr before declining over the following 36 hr. As the solar particle event flux was graduall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 12 publications
(18 reference statements)
2
45
1
Order By: Relevance
“…At Mars a GLE event was also observed. As reported by Zeitlin et al (), Ehresmann et al (), and Guo, Dumbovic, et al (), MSL/RAD observed enhancements in the surface radiation dose rates and particles fluxes beginning at 19:50 UT on 10 September 2017, making this event the first simultaneous GLE observation at two planets. Located at the Gale Crater, MSL/RAD has been continuously measuring the radiation environment at the surface since 2012 (Hassler et al, ).…”
Section: Seps At Marssupporting
confidence: 75%
See 1 more Smart Citation
“…At Mars a GLE event was also observed. As reported by Zeitlin et al (), Ehresmann et al (), and Guo, Dumbovic, et al (), MSL/RAD observed enhancements in the surface radiation dose rates and particles fluxes beginning at 19:50 UT on 10 September 2017, making this event the first simultaneous GLE observation at two planets. Located at the Gale Crater, MSL/RAD has been continuously measuring the radiation environment at the surface since 2012 (Hassler et al, ).…”
Section: Seps At Marssupporting
confidence: 75%
“…For the surface dose rates, MSL/RAD observed factors of 2–3 increase above the GCR‐induced background levels (Zeitlin et al, ). In terms of the radiation hazards posed by SEPs, the integrated dose over a 30‐day interval including the SEP period was well below the NASA exposure limits for astronauts (Zeitlin et al, ). Figure m shows the measured dose rates from the MSL/RAD‐E (plastic) detector.…”
Section: Seps At Marsmentioning
confidence: 99%
“…In comparison to the ISS, MSL‐RAD on the surface of Mars observed a dose rate of 0.4 μGy/min at the time of the second “main” peak of the event 07:30 UTC on 11 September 2017, while the onset of the event was already seen on 10 September at around 19:50 UTC. The total dose from the event observed with the MSL‐RAD B subdetector was 418 μGy in Si (Ehresmann et al, ; Hassler et al, ; Zeitlin et al, ).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…The onset of the event was measured by MSL‐RAD on the surface of Mars on 10 September at around 19:50 UTC (Ehresmann et al, ; Zeitlin et al, ) about 4 hr after the onset at Earth. The total dose measured with the MSL‐RAD B detectors amounts to 418 μGy in Si for the event (Zeitlin et al, ) which is less than twice the daily dose from GCR.…”
Section: Calculated Radiation Exposures During the Eventmentioning
confidence: 99%